Une approche de l’étude du droit et du colonialisme : vers une perspective autohistorique amérindienne sur le changement juridique, la colonisation, les sexes et la résistance à la colonisation - Smandych, Russell; Lee, Gloria (Criminologie, 1995)
This paper outlines the theoretical perspective we have developed to guide the research we are undertaking on law and colonialism in the Canadian west. Although developed specifically as a tool for defining the theoretical boundaries of our own research, this theoretical perspective may be applied more generally by researchers involved in research on the history of law and social control in colonial societies. The theoretical perspective that we propose is grounded in theoretical and empirical work from a number of different fields, including the history and sociology of social control, the study of legal pluralism, and the study of the process of colonization as it has been approached in recent years by feminist scholars and First Nations historians. The purpose of this paper is to show how this new Amerindian autohistorical perspective can be used to help generate research on the interconnected issues of legal change, colonization, gender, and resistance.